Characteristics of Postnatal Ontogenetic Changes in Small Oval Follicles of the Thyroid Gland in Hissar Sheep from Regions with Different Levels of Iodine Deficiency - Mamasoliyevich, Allamurodov Oybek; Babakulovich, Dilmurodov Nasriddin (American Journal of Biodiversity, 2026)
The dynamics of changes in the morphometric dimensions of the histological structures of the thyroid gland in sheep raised under natural conditions with varying levels of iodine deficiency were investigated during postnatal ontogenesis. It was found that the absolute diameter of small oval follicles in the right and left lobes of the thyroid gland in sheep from the Kashkadarya and Fergana regions decreased stepwise from the first 3 days to 60 months of postnatal ontogenesis. In addition, it was established that at all studied stages after 3 months of postnatal development, the absolute diameter of small oval follicles in sheep raised in the Fergana region was higher than that observed in sheep from the Kashkadarya region.